2001
DOI: 10.1046/j.1365-3148.2001.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet chemokines and their receptors: what is their relevance to platelet storage and transfusion practice?

Abstract: The role of platelets as inflammatory cells is demonstrated by the fact that they can release many growth factors and inflammatory mediators, including chemokines, when they are activated. The best known platelet chemokine family members are platelet factor 4 (PF4) and beta-thromboglobulin (beta-TG), which are synthesized in megakaryocytes, stored as preformed proteins in alpha-granules and released from activated platelets. However, platelets also contain many other chemokines such as interleukin-8 (IL-8), gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 150 publications
(219 reference statements)
1
127
0
3
Order By: Relevance
“…RANTES is one of the chemokines produced by cultured human PBMC (Denison et al, 1997). It has also been reported that platelets release RANTES and MIP-1α following activation (Boehlen and Clemetson, 2001). Moreover, we recently demonstrated that PBMC-conditioned medium can promote the invasion of BeWo cells, a trophoblastic cell line (Egawa et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…RANTES is one of the chemokines produced by cultured human PBMC (Denison et al, 1997). It has also been reported that platelets release RANTES and MIP-1α following activation (Boehlen and Clemetson, 2001). Moreover, we recently demonstrated that PBMC-conditioned medium can promote the invasion of BeWo cells, a trophoblastic cell line (Egawa et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…PF4 is also released from activated T lymphocytes and mast cells (21). It has been shown to influence numerous other biological properties, including inhibiting endothelial cell proliferation, migration, and angiogenesis (22)(23)(24), inhibiting T cell function by down-modulating cell proliferation and cytokine release (25), and supporting the survival of normal hematopoietic precursors and protecting them from the toxicity of chemotherapeutic agents (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the specific ligands for CCR4, CCL17 (thymus and activation-regulated chemokine) and CCL22 (macrophage-derived chemokine) (19), reportedly induce migration of both Th2 and Th1 cells in vitro (20,21). Finally, the receptor is not limited to T cells because CCR4 mRNA is reportedly expressed by platelets, NK cells, macrophages, and dendritic cells (DCs) (22)(23)(24)(25). In view of these reports, it is clear that the role of CCR4 with regard to T cell function needs better definition.…”
Section: T He Cd4mentioning
confidence: 99%